EEG slow wave sleep and slow wave activity in extended sleep with bright light induced phase shifts of core body temperature. - Christ, Gregory J. (University of Ottawa (Canada), 1994)
In this study, the time courses of slow wave sleep (SWS) and EEG slow wave activity (SWA) were examined in relation to core body temperature (CBT) during extended sleep periods of 15 hours. This investigation examined the merits of a hypothetical 12-hour rhythm of SWS to: (1) confirm its existence; (2) see if it was reflected by the more objective measure of SWA (power spectral analysis); and (3) determine if there was any relationship between this 12-hour rhythm and the CBT rhythm. In Study 1, 7 subjects (age 18-22 years) slept in the laboratory for 3 consecutive nights (2 of 8 hours, then 1 of 15 hours). Rectal CBT was monitored during sleep periods. The main findings were that SWS and SWA both significantly increase in the final 3-hour block over the center 3-hour block, and that these late increases were not related to waking after sleep onset (WASO) or rapid eye movement (REM) sleep. Five of the 7 subjects showed a return of SWA, which was defined by the maximum 15 minute running average in the last 5 hours exceeding the same measure for the previous 4 hours (about 2 sleep cycles with lower SWA). With CBT phase defined as the delay from sleep onset to CBT minimum, it was found that late SWS (in the last 3 hours), and magnitude of the SWA return had significant positive relationships to CBT phase. In Study 2, 3 subjects (age 19, 21, and 29) were studied for 4 series of 4 consecutive nights, with bedtime at 23:30h on all nights. Two series served as baseline (8HBL, and 6HBL). During one series (ML) CBT rhythm was phase advanced using morning bright light (7000-11000 lux, 6:00h-9:00h), and during another series (EL) CBT was delayed using evening bright light (20:00h-23:00h). Subjects were kept in dim light (250 lux) during these morning and evening periods for the 8HBL and 6HBL. A range of CBT phase to sleep timing combinations resulted, with ML always phase advanced relative to EL. CBT phase plotted against late SWS and SWA measures showed a positive association between CBT phase and timing of SWA return (except in one subject (#3)), and a smaller positive association to SWA in the last 3 hours (except in one subject (#1)). When data from Study 1 and the equivalent 8HBL of Study 2 were combined, SWS and SWA late in the sleep period were not significantly related to WASO or REM, and magnitude of the SWA return was statistically significant. There was also a significant relationship between CBT phase and late SWS, magnitude of SWA return, and timing of the SWA return, but not with SWA in the last 3 hours. The data were consistent with a 12-hour rhythm of SWS and SWA, in which the minor pole does not depend solely on WASO or REM, and is related in timing and magnitude to the CBT rhythm. Magnitude of both poles are likely influenced by prior amounts of waking, but the special conditions of extended sleep illustrate the association of the minor pole to the CBT rhythm.
Keywords: Psychology, Psychobiology.